Glucose, Ketone and Protein Profile in Diabetes Mellitus Patients Using Urine Strip Test at the Regional Health Laboratory UPTD of Samarinda City - Hidayati, Nurul (Jurnal Sains dan Teknologi Laboratorium Medik, 2024)
Diabetes mellitus is a disease of the metabolic system with the characteristics of hyperglycemia (an increase in blood sugar levels that exceed normal limits) which is caused by abnormalities in the body's insulin secretion, abnormalities in insulin action or even both. Currently, it is estimated that 25 million or around 9.3% of Indonesia's population in 2020 will experience impaired kidney function due to hypertension and diabetes. The aim of this study was to determine the profile of glucose, ketones and protein in diabetes mellitus sufferers using a urine strip test at the UPTD Regional Health Laboratory of Samarinda City. The type of research used is descriptive. The research population was prolanis patients who had been diagnosed with diabetes mellitus and had their urine checked at the UPTD Regional Health Laboratory of Samarinda City. The samples were Prolanis participants suffering from diabetes mellitus who were examined for urine glucose, ketones and protein using the urine strip test method. The results of the research were that in the urine glucose examination, 4 samples (13%) had 1 positive result and 5 samples (17%) had 2 positive results. In the urine ketone examination, 1 sample (3%) had a positive result of 1. In the urine protein examination, 3 samples (10%) had 1 positive result and 2 samples (7%) had 4 positive results.